Health sector reform processes in Nigeria: A review of factors that have enabled or constrained policy implementation in Enugu and Anambra States of Nigeria - B S C Uzochukwu; O E Onwujekwe; O P Ezeoke; N P Uguru; U Ezeoke; M N Ajuba (International Journal of Medicine and Health Development, 2010)
Introduction: In most countries health care reform is aimed at improving the efficiency, equity and effectiveness of the health sector. Documentation of health sector reform experiences has focused primarily on efficiency and design of reforms, largely neglecting equity and the frequent experience that reforms are not fully implemented. The reasons why implementation stalls remain rarely explored in the health sector. This review assesses the factors that have enabled or constrained health sector reforms in Enugu and Anambra states of Nigeria. Methods: A systematic search of literature published from 1990-2008 was conducted. Grey literature (conference papers, technical reports, dissertations, etc), journal articles, abstracts, relevant books and internet articles were reviewed. Results: The results show that the following reforms have been attempted in Enugu and Anambra states of Nigeria in the past two decades: The Bamako initiative program and drug revolving funds with user fees and exemption system, reproductive health reform, integrated management of childhood illnesses (IMCI), district health system, community-based health insurance ,immunization and disease- specific programs. Only a small number of core articles focus on these reforms and their impact on equity. Some of the key factors which have determined whether these reforms preferentially benefit the poorest have also been outlined and they range from institutional, political, managerial to contextual factors. Conclusions: Some of the key factors which have determined whether reforms preferentially benefit the poorest have been outlined. If the enabling factors are enforced and the deterring factors corrected, the chances of achieving the MDGs goals through these health reforms will be strengthened.